2018
DOI: 10.37358/mp.18.3.5040
|View full text |Cite
|
Sign up to set email alerts
|

It is Useful to Use Plastic Anatomical Models in Teaching Human Anatomy ?

Abstract: The classical method of teaching human anatomy to students is based on the dissection of human cadavers. Nowadays, there are many ethical controversy regarding the use of human cadavers during anatomy courses. In our study we tried to get undergraduate students� opinion about some different techniques of teaching human anatomy, including the utility of plastic models. We introduced in this study 163 students in the first year of their study at the Faculty of General Medicine from the University of Medicine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Most studies published in recent years have highlighted the importance of inflammatory syndrome in the pathogenesis of various cancers, including colorectal cancer [19]. It has also been demonstrated that the severity of the systemic inflammatory syndrome affects the prognostic of these patients [20][21][22]. At the same time, some authors have proven that chronic inflammatory syndrome stimulates the growth of malignant tumors as well as the metastatic process [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies published in recent years have highlighted the importance of inflammatory syndrome in the pathogenesis of various cancers, including colorectal cancer [19]. It has also been demonstrated that the severity of the systemic inflammatory syndrome affects the prognostic of these patients [20][21][22]. At the same time, some authors have proven that chronic inflammatory syndrome stimulates the growth of malignant tumors as well as the metastatic process [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with BCLC B-stage who benefit from TACE and another alternative therapy (eg, RFA) may be associated with or exhibit tumor stagnation, or tumor necrosis in most cases [26]. In C stages BCLC, desperate cases -the two patients to whom TACE was the last therapeutic attitude, despite the predicted prognosis, TACE assured the prolongation of life and increased life quality [27][28][29]. In the majority of patients in this study, stage A BCLC, chemoembolization was a therapeutic attitude that allowed subsequent liver transplantation (when it was not Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, more and more types of heterologous materials are used in medicine, both in tissue repair techniques and in various simulation or learning techniques. Such an example is given by the use of surgical meshes made out of plastic materials [10][11][12].…”
Section: Resultsmentioning
confidence: 99%